2017
DOI: 10.1093/mnras/stx2602
|View full text |Cite
|
Sign up to set email alerts
|

Observability of forming planets and their circumplanetary discs – I. Parameter study for ALMA

Abstract: There are growing amount of very high-resolution polarized scattered light images of circumstellar disks. Naturally, the question arises whether the circumplanetary disk forming around nascent planets can be detected with the same technique. Here we created scattered light mock observations at 1.2 and 1.6 microns for instruments like SPHERE and GPI, for various planetary masses and disk inclinations. We found that the detection of a circumplanetary disk is significantly favored if the planet is massive (≥ 5M J… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 70 publications
5
52
0
Order By: Relevance
“…• The CPD mass upper limit is enough to be incompatible with several planet accretion models, while synthetic observations of numerical simulation by Szulágyi et al (2018) provide a CPD flux similar to the upper limit reported here. Gas-starved models are also still compatible.…”
Section: Discussionsupporting
confidence: 59%
“…• The CPD mass upper limit is enough to be incompatible with several planet accretion models, while synthetic observations of numerical simulation by Szulágyi et al (2018) provide a CPD flux similar to the upper limit reported here. Gas-starved models are also still compatible.…”
Section: Discussionsupporting
confidence: 59%
“…Marley et al 2007;Mordasini et al 2012;Mordasini 2013;Baruteau et al 2016). The estimated temperatures are similar to the temperatures of the accretion shock around planets formed by core accretion (Marleau et al 2017(Marleau et al , 2019Szulágyi 2017;Szulágyi et al 2018;Szulágyi & Mordasini 2017) and therefore their circumplanetary discs are also expected to be relatively hot. These high temperatures contradict the results of the disc instability model presented in , as in the simulations presented here we were able to follow the collapse of a fragment at much higher densities and capture the formation of the first and second core.…”
Section: The Properties Of Protoplanets Formed Around M Dwarfs By Dissupporting
confidence: 55%
“…A timespan of about 1 week would be enough to observe the proper motion of a circumplanetary disk detected with the same signal-to-noise ratio but at an orbital radius of 1 au. Similar predictions for the expected circumplanetary disk fluxes at these wavelengths are derived from the α−models of Zhu et al (2017), whereas significantly brighter fluxes are obtained if adiabatic compression due to the accretion process is the main heating mechanism in these systems (Szulágyi et al 2016(Szulágyi et al , 2017. Brighter circumplanetary disks, up to ∼ 100 µJy at 3 mm, are expected also around planets further from the star, where the Hill radius, and therefore the expected disk radius as well, are larger .…”
Section: Different Distances From Earthsupporting
confidence: 72%